The Effect of Jumping Game Modification on Jumping Learning Outcomes in Elementary School - Salsabiila, Yusrina; Andrijanto, Doni; Johanis, Feri (Champions: Education Journal of Sport, Health, and Recreation, 2025)
PE learning in schools will be optimal if the available facilities and infrastructure are adequate. However, at the research site where I conducted, the facilities for PE are limited. Therefore, this study aims to increase students' movement experience through game modification. It is hoped that this activity can improve student learning outcomes, both in cognitive and psychomotor aspects. This study aims to determine the effect of game modification on basic movement learning outcomes in grade 5 students of SDN Gading 1 Surabaya. This study uses the purposive sampling method, where samples are selected based on certain criteria to suit the research objectives. The sample used was 30 5B grade students of SDN Gading 1 Surabaya. Data was collected through knowledge and skill tests with treatment in the form of game modifications. Data analysis was carried out using descriptive statistics, including averages, standard deviations, and variances, as well as inferential statistics with normality tests, t-tests, and improvement measurements. The results showed that game modification had an influence of 30% on psychomotor tests and 45% on students' cognitive tests.